Impact of switching from the 2009 to the 2021 CKD-EPI Equation for eGFR. (9th November 2022) - Bailey, Cedric; Farnsworth, Christopher
Abstract: Recent national and international guidelines have recommended implementing the 2021 CKD-EPI equation for estimating glomerular filtration rate (eGFR). Relative to the 2009 CKD-EPI equation, the 2021 equation eliminates race-based modifiers in the calculation of eGFR based on a remodeling of the original CKD-EPI dataset. Further, updated guidelines now recommend integrating Cystatin C as a confirmatory test in all patients with an eGFR between 45-59 mL/min/1.73m 2 . Here we assess the impact of switching from the 2009 CKD-EPI creatinine-based equation to the 2021 CKD-EPI creatinine-based equation on both non-black and black populations and assess the feasibility of implementing a reflex for Cystatin C on all patients with an eGFR between 45-59 mL/min/1.73m 2 . The laboratory information system was queried retrospectively from 11/01/2021 to 12/31/2021 for age, sex, self-identified ethnicity, and serum creatinine concentrations from basic/comprehensive metabolic panels and renal panels. Slope and linearity of the reported eGFR with the 2009 and 2021 equations were compared using Deming regression and Fisher's exact test was used to assess the proportion of eGFR results <30 ml/min/1.73m 2 and between 45-59 ml/min/1.73m 2 . Of the 64, 657 serum creatinine values, 37, 589 were from self-identifying non-black patients and 27, 068 were from self-identifying black patients. Deming regression revealed a slope of 0.997 (95% CI; 0.997-0.998) and intercept of 2.69 (2.65-2.74) for the non-black population and a slope of 0.863 (0.862-0.864) and intercept of 2.451 (2.39-2.51) for the black population. The number of non-black individuals with an eGFR <30 mL/min/1.73m 2 decreased 5622 to 5060 (p<0.001) and black patients increased from 4018 to 4387 (p<0.001). The number of non-black individuals with an eGFR in the range of 45-59 ml/min/1.73m 2 increased marginally from 4, 410 (11.7%) to 4, 525(12.0%, p=0.19) and the number of black individuals increased from 2, 501 (9.2%) to 3, 299 (12.2%, p<0.001). If a Cystatin C reflex test was performed on all patients with an eGFR between 45-59 mL/min/1.73m 2, 2325 assays would have been performed on out-patients and 5499 on in-patients. These results, in the context of recently updated guidelines imply that the changing from the 2009 CKD-EPI equation to the 2021 CKD-EPI equation is likely to increase the proportion of black individuals diagnosed with moderate to severe and severe loss of kidney function more so than the non-black populations. Implementation of a Cystatin C reflex on all patients with an eGFR between 45-59 mL/min/1.73m 2 is likely to lead to considerable overuse and should be limited to out-patients and physician ordered tests.